2019
DOI: 10.4103/ortho.ijortho_551_18
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Microbiological Study of Prosthetic Joint Infections in an Indian Tertiary Care Hospital: Role of Universal 16S rRNA Gene Polymerase Chain Reaction and Sequencing in Diagnosis

Abstract: Background: We determined the magnitude and clinico-microbiological profile of prosthetic joint infection (PJI) at a tertiary hospital. The diagnostic potential of 16S rRNA gene polymerase chain reaction (PCR) and sequencing on periprosthetic tissue samples was evaluated for the diagnosis of PJI. Materials and Methods: This ambispective cohort study consisted of patients who underwent primary or revision hip or knee arthroplasty from June 2013 to June 2017. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 26 However, the sensitivity of the JI panel may be subjective and dependent on the country in which the JI panel technology is offered. 27 - 29 …”
Section: Discussionmentioning
confidence: 99%
“… 26 However, the sensitivity of the JI panel may be subjective and dependent on the country in which the JI panel technology is offered. 27 - 29 …”
Section: Discussionmentioning
confidence: 99%
“…Although data were obtained from single centers, recently Villa et al reported a similar trend from 6 countries covering 3 continents [ 18 ]. Few studies reported contradictory findings with approximately two-thirds of Gram-negative PJIs (GN-PJIs) [ 4 , 19 ]. All these studies were conducted at single speciality centers and the majority of the cases were referred cases from other hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on microbial profiles of infected primary TKAs but the majority are limited by a small sample size, being single-center studies, microbial profile description based on type of PJI or type of surgical management [ 3 , 4 ]. Though the previous three studies using Swedish Knee Arthroplasty Register (SKAR) data have shown the predominance of Gram-positive bacteria in knee PJIs, there are no recent reports on the microbial profile of primary TKA infections from Sweden [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%